Pengembangan Model Intervensi Dini bagi Anak Berperilaku Mengganggu (Disruptive Behavior) pada PAUD di Desa Menayu, Kabupaten Magelang - Purwati Purwati; Dewi Lianasari (Indonesian Journal of Educational Counseling, 2019)
DEVELOPMENT OF THE EARLY INTERVENTION MODEL FOR CHILDREN DISRUPTIVE BEHAVIOR IN PAUD OF MENAYU, MAGELANG REGENCY. Children with all potential are the next generation that needs to be stimulated according to their stages and characteristics. Disruptive behavior in children is a negative behavior that is harmful to themselves and others. Children's internal and external factors cause the formation of disruptive behavior. This study aims to find out the profile of disturbing child behavior and the formulation of early childhood intervention models that interfere with behavior. Data collection in this study uses observation and Focus Group Discussion. Observations are made on children using the "time sampling" or "sampling interval" approach, and the FGD is imposed on PAUD educators. The research method uses research and development approaches. The research subjects were 50 children and 10 PAUD educators. The results of research on profiles of disturbing behavior of children indicate: (1) fighting 54%; (2) grabbing friends toys 60%; (3) do not want to sit quietly (walk) 54%; (4) screaming and crying 48%; and (5) do not want to be left by parents / caregivers 40%. Early childhood intervention models that interfere with behavior can be used by educators (formal, non-formal, and informal) in giving treatment to children who show disturbing behavior. Implementation of appropriate early interventions can optimize all potential children.